2022
DOI: 10.1186/s13054-022-04006-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic concordance between BioFire® FilmArray® Pneumonia Panel and culture in patients with COVID-19 pneumonia admitted to intensive care units: the experience of the third wave in eight hospitals in Colombia

Abstract: Background The detection of coinfections is important to initiate appropriate antimicrobial therapy. Molecular diagnostic testing identifies pathogens at a greater rate than conventional microbiology. We assessed both bacterial coinfections identified via culture or the BioFire® FilmArray® Pneumonia Panel (FA-PNEU) in patients infected with SARS-CoV-2 in the ICU and the concordance between these techniques. Methods This was a prospective study of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…The prevalence of influenza A virus coinfection in our study was higher than that reported in previous studies of hospitalized patients from Peru and Colombia, where this pathogen was not detected ( 22 , 62 ). Furthermore, our data showed that patients with influenza co-infection had a higher risk of respiratory symptoms, such as wheezing, and other symptoms, such as dizziness and chills.…”
Section: Discussioncontrasting
confidence: 90%
“…The prevalence of influenza A virus coinfection in our study was higher than that reported in previous studies of hospitalized patients from Peru and Colombia, where this pathogen was not detected ( 22 , 62 ). Furthermore, our data showed that patients with influenza co-infection had a higher risk of respiratory symptoms, such as wheezing, and other symptoms, such as dizziness and chills.…”
Section: Discussioncontrasting
confidence: 90%
“…Unfortunately, standard clinical diagnostic criteria for VAP are invalid in the critical COVID-19 population [ 40 , 41 ]. Against this background, shortening the time from sampling to pathogen identification, and the use of multiplex PCR pneumonia panels have been proposed in COVID-19 patients to improve detection of VAP [ 24 , 42 ]. Research is now in progress on the use of procalcitonin (PCT) to distinguish between viruses and bacteria as etiologic agents of VAP [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It offers high sensitivity and short turnaround time, showing great potential for optimizing therapy and improving antibiotic stewardship [ 30 , 31 ]. BAL FAPPP has already proved to be highly concordant to conventional culture (> 90%) in diagnosing bacterial coinfection among COVID-19 patients at ICU admittance [ 32 ]. In our cohort, its primary clinical limitation was related to the relevant proportion of Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%